The Extent to which Teachers Use the Skills and Knowledge Acquired in the Information and Communication Technology (ICT) Higher Education Diploma Program in the Classroom - Al Bakheet, Rasheen; Al Omari, Akram (Jordan Journal of Educational Sciences, 2008)
The purpose of this study was to identify the degree to which Information and Communication Technology (ICT) skills and knowledge are practiced by ICT teachers in their classroom teaching. A sample of twenty teachers (10 males and 10 females) holding the Higher Diploma in Information & Communication Technology (ICT) for the year 2006/2007 in Irbid Governorate were randomly selected and observed in their classrooms. Their teaching activities in their classrooms were recorded twice on video. A checklist that was designed and developed by the researchers with an adequate validity and reliability was then employed. The results showed that ICT teachers moderately practiced ICT skills and knowledge in three functions in their classroom teaching: planning, classroom management and feedback. Their uses of ICT in executing educational classroom activities were minimal. Furthermore, no statistical significant differences at (α ≥ 0.05) were found between means attributed to gender and academic specialization